Influenza virus decreases albumin uptake and megalin expression in alveolar epithelial cells - Alberro-Brage, Andrés; Kryvenko, Vitalii; Malainou, Christina; Günther, Stefan; Morty, Rory E.; Seeger, Werner; Herold, Susanne; Samakovlis, Christos; Vadász, István (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome (ARDS) is a common complication of influenza virus (IV) infection. During ARDS, alveolar protein concentrations often reach 40-90% of plasma levels, causing severe impairment of gas exchange and promoting deleterious alveolar remodeling. Protein clearance from the alveolar space is at least in part facilitated by the multi-ligand receptor megalin through clathrin-mediated endocytosis. To investigate whether IV infection impairs alveolar protein clearance, we examined albumin uptake in MLE-12 cells and alveolar epithelial cells (AEC) from murine precision-cut lung slices (PCLS), under IV infection conditions. Our results showed that IV significantly downregulated albumin uptake, independently of activation of the TGF-β1/GSK3β axis that has been previously implicated in the regulation of megalin function. We found that decreased plasma membrane abundance, total protein levels, and mRNA expression of megalin were associated with this phenotype. When we analyzed AEC of IV-infected mice, we found similar levels of megalin downregulation, and identified a significant upregulation of matrix metalloproteinase (MMP)-14 in broncho-alveolar lavage (BAL) fluid cells. We found that the specific inhibition of this protease partially recovered total megalin levels and albumin uptake, suggesting that the previously described MMP-driven shedding mechanisms are potentially involved in downregulation of megalin cell surface abundance and clearance of excess alveolar protein. As lower alveolar edema protein concentrations are associated with better outcomes in respiratory failure, our findings highlight the therapeutic potential of a timely MMP inhibition in the treatment of IV-induced ARDS.